Effects of awareness of breast cancer overdiagnosis among women with screen-detected or incidentally found breast cancer: a qualitative interview study - Brooke Nickel; Alexandra Barratt; Kirsten McCaffery; Kristen Pickles; Jolyn Hersch; Jayant S Vaidya (BMJ Open)
Objectives To explore experiences of women who identified themselves as having a possible breast cancer overdiagnosis.Design Qualitative interview study using key components of a grounded theory analysis.Setting International interviews with women diagnosed with breast cancer and aware of the concept of overdiagnosis.Participants Twelve women aged 48–77 years from the UK (6), USA (4), Canada (1) and Australia (1) who had breast cancer (ductal carcinoma in situ n=9, (invasive) breast cancer n=3) diagnosed between 2004 and 2019, and who were aware of the possibility of overdiagnosis. Participants were recruited via online blogs and professional clinical networks.Results Most women (10/12) became aware of overdiagnosis after their own diagnosis. All were concerned about the possibility of overdiagnosis or overtreatment or both. Finding out about overdiagnosis/overtreatment had negative psychosocial impacts on women’s sense of self, quality of interactions with medical professionals, and for some, had triggered deep remorse about past decisions and actions. Many were uncomfortable with being treated as a cancer patient when they did not feel ‘diseased’. For most, the recommended treatments seemed excessive compared with the diagnosis given. Most found that their initial clinical teams were not forthcoming about the possibility of overdiagnosis and overtreatment, and many found it difficult to deal with their set management protocols.Conclusion The experiences of this small and unusual group of women provide rare insight into the profound negative impact of finding out about overdiagnosis after breast cancer diagnosis. Previous studies have found that women valued information about overdiagnosis before screening and this knowledge did not reduce subsequent screening uptake. Policymakers and clinicians should recognise the diversity of women’s perspectives and ensure that women are adequately informed of the possibility of overdiagnosis before screening.